Wiiw studies on the integration of Middle Eastern refugees in Austria, based on FIMAS surveys and register-based labour market career data - Michael Landesmann; Sandra M. Leitner; Stefan Jestl; Maryna Tverdostup; Sebastian Leitner; Isilda Mara (The Vienna Institute for International Economic Studies (wiiw), 2023)
This Policy Note reports on the analyses undertaken in a number of wiiw Working Papers that are the output of two projects financed by the Anniversary Fund of the Austrian National Bank (Project no. 18474 and no. 17166). Four of the papers are based on survey data from the FIMAS dataset, which has been compiled over the years by the International Centre for Migration Policy Development (ICMPD), together with wiiw, and which document the experiences of recent waves of refugees from Afghanistan, Iran, Iraq and Syria. The topics covered in these four papers are as follows. First, an analysis of the pattern of occupational status loss (or gain) that refugees experience in the course of the move from their home countries to the destination country (Austria), focusing on the move from the jobs they had prior to the move, to their first job in Austria and then to their second or current job. Second, an examination of the effectiveness of two of the labour market integration programmes offered by the Austrian public employment service (AMS): the Competence Check and the Voluntary Integration Year programme. Third, an investigation into the interrelationships between aspects of the 'social integration' and the 'labour market integration' of refugees. Fourth, an analysis of the factors determining (or related to) the mental health problems that this wave of refugees has had to cope with. A fifth paper is based on the register-based labour market career data provided by Statistics Austria: it examines a number of issues (job entry, job quality, job stability) related to the trajectories of refugees' labour market experiences in Austria, compared to other non-European migrants from low- and medium-income countries.
Keywords: C13; C41; F22; H43; I10; J15; J24; J62; J68; 330; Refugees; labour market integration; occupational trajectories; refugee integration programmes; social integration; mental health